2020
DOI: 10.1038/s41586-020-2312-y
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenicity of SARS-CoV-2 in hACE2 transgenic mice

Abstract: Cite this article as: Bao, L. et al. The pathogenicity of SARS-CoV-2 in hACE2 transgenic mice. Nature https://doi.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
721
1
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,054 publications
(777 citation statements)
references
References 9 publications
44
721
1
11
Order By: Relevance
“…19 In addition, viral antigens were also detected in macrophages infiltrated into the alveolar interstitium and cavities of SARS-CoV-2-infected hACE2-expressing mice. 20 Moreover, immunofluorescent double staining showed that IL-6 is primarily produced by infected macrophages. 17 These observations suggest that SARS-CoV-2 can also enter into monocytes/macrophages, 21 possibly through the Fc receptor.…”
Section: Ade Can Explain Characteristics Of Severe Covid-19mentioning
confidence: 99%
“…19 In addition, viral antigens were also detected in macrophages infiltrated into the alveolar interstitium and cavities of SARS-CoV-2-infected hACE2-expressing mice. 20 Moreover, immunofluorescent double staining showed that IL-6 is primarily produced by infected macrophages. 17 These observations suggest that SARS-CoV-2 can also enter into monocytes/macrophages, 21 possibly through the Fc receptor.…”
Section: Ade Can Explain Characteristics Of Severe Covid-19mentioning
confidence: 99%
“…Four other hACE2-expressing mouse lines have been created to date and tested for the ability to support SARS-CoV-2 infection (Lutz, 2020). Two lines express the hACE2 gene under the control of the mouse ACE2 promotor (Bao et al, 2020); one was made using CRISPR/Cas9 technology (Sun et al, 2020). The third strain uses the lung ciliated epithelial cell HFH4 promoter (Menachery et al, 2016) (Dinnon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, no monkey developed severe symptoms during the study [58]. In a study using a mouse model, transgenic mice with human ACE2 expression, but not wild-type mice, were found to be susceptible to SARS-CoV-2 infection [59]. Mice inoculated with SARS-CoV-2 through the intranasal route had a 5-10% loss of body weight and histopathology in the lung, such as interstitial pneumonia and infiltration of immune cells.…”
Section: In Vivo Models For Testing Sars-cov-2 Neutralizing Antibodiesmentioning
confidence: 98%
“…Monkey and mouse models have been reported for testing SARS-CoV-2-neutralizing antibodies [58][59][60]. In the monkey study, researchers found that rhesus macaques infected with SARS-CoV-2 through the intratracheal route had mild illness, and their lungs showed signs of pneumonia similar to those in humans with COVID-19 [58].…”
Section: In Vivo Models For Testing Sars-cov-2 Neutralizing Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation